Children’s Responses to the Rubber-Hand Illusion Reveal Dissociable Pathways in Body Representation - Cowie, Dorothy; Makin, Tamar R.; Bremner, Andrew J. (Psychological Science, 2013)
The bodily self is constructed from multisensory information. However, little is known of the relation between multisensory development and the emerging sense of self. We investigated this question by measuring the strength of the rubber-hand illusion in young children (4 to 9 years old) and adults. Intermanual pointing showed that children were as sensitive as adults to visual-tactile synchrony cues for hand position, which indicates that a visual-tactile pathway to the bodily self matures by at least 4 years of age. However, regardless of synchrony cues, children’s perceived hand position was closer to the rubber hand than adults’ perceived hand position was. This indicates a second, later-maturing process based on visual-proprioceptive information. Furthermore, explicit feelings of embodiment were related only to the visual-tactile process. These findings demonstrate two dissociable processes underlying body representation in early life, and they call into question current models of body representation and ownership in adulthood.
EPrint Processing Status: Full text deposited in DRO